Scenario-based modeling of land-use and land-cover changes to promote sustainability in biosphere reserves: a case study from North Vidzeme, Latvia - Krumins, Janis; Klavins, Maris (Frontiers in Remote Sensing, 2025)
Biosphere reserves serve as critical areas for balancing conservation with sustainable development. This study investigates land-use and land-cover changes in the North Vidzeme Biosphere Reserve (Latvia) from 1990 to 2018, employing scenario-based modeling to project future trends. Historical analyses reveal overall stability but highlight cyclical agricultural intensification and extensification, forest decline, and expansions in transitional woodland-shrub. Four scenarios—business-as-usual, sustainable development, climate adaptation and mitigation, and conservation-oriented—were evaluated for their ecological and socio-economic implications. Business-as-usual scenario continues historical trends of moderate urban growth and agricultural intensification, risking limited restoration gains. In contrast, sustainable development and climate adaptation and mitigation scenarios emphasize reforestation, biodiversity improvement, and climate resilience, aligning with the European Union 2030 Biodiversity Strategy. Conservation-oriented scenario prioritizes stabilization and minimizing anthropogenic pressures yet lacks proactive restoration measures. Statistical tests confirm that socio-economic factors, zoning, and landscape richness significantly drive land-use and land-cover changes, with most changes adhering to the North Vidzeme Biosphere Reserve regulations. However, certain non-compliant changes, such as forest-to-agriculture conversions, highlight the need for stronger enforcement. While ecological impacts such as land-use transitions, biodiversity shifts, and conservation compliance were considered, socio-economic implications were primarily discussed in relation to zoning and land-use trends rather than through a standalone analysis. These scenario-based insights offer valuable guidance for adaptive land management in protected areas.